Combined application of biofertilizers and inorganic nutrients improves sweet potato yields - Mukhongo, Ruth Wilhem; Tumuhairwe, J.B.; Ebanyat, Peter; AbdelGadir, Abdel Aziz H.; Thuita, Moses N.; Masso, C. (Frontiers Media, 2017)
Sweet potato [Ipomoea batatas (L) Lam] yields currently stand at 4.5 t ha−1 on smallholder farms in Uganda, despite the attainable yield (45–48 t ha−1) of NASPOT 11 cultivar comparable to the potential yield (45 t ha−1) in sub-Saharan Africa (SSA). On-farm field experiments were conducted for two seasons in the Mt Elgon High Farmlands and Lake Victoria Crescent agro-ecological zones in Uganda to determine the potential of biofertilizers, specifically arbuscular mycorrhizal fungi (AMF), to increase sweet potato yields (NASPOT 11 cultivar). Two kinds of biofertilizers were compared to different rates of phosphorus (P) fertilizer when applied with or without nitrogen (N) and potassium (K). The sweet potato response to treatments was variable across sites (soil types) and seasons, and significant tuber yield increase (p < 0.05) was promoted by biofertilizer and NPK treatments during the short-rain season in the Ferralsol. Tuber yields ranged from 12.8 to 20.1 t ha−1 in the Rhodic Nitisol (sandy-clay) compared to 7.6 to 14.9 t ha−1 in the Ferralsol (sandy-loam) during the same season. Root colonization was greater in the short-rain season compared to the long-rain season. Biofertilizers combined with N and K realized higher biomass and tuber yield than biofertilizers alone during the short-rain season indicating the need for starter nutrients for hyphal growth and root colonization of AMF. In this study, N0.25PK (34.6 t ha−1) and N0.5PK (32.9 t ha−1) resulted in the highest yield during the long and the short-rain season, respectively, but there was still a yield gap of 11.9 and 13.6 t ha−1 for the cultivar. Therefore, a combination of 90 kg N ha−1 and 100 kg K ha−1 with either 15 or 30 kg P ha−1 can increase sweet potato yield from 4.5 to >30 t ha−1. The results also show that to realize significance of AMF in nutrient depleted soils, starter nutrients should be included.